Presentation of Autoantigen in Peripheral Lymph Nodes Is Sufficient for Priming Autoreactive CD8+ T Cells - Honke, Nadine; Shaabani, Namir; Teijaro, John R.; Christen, Urs; Hardt, Cornelia; Bezgovsek, Judith; Lang, Philipp A.; Lang, Karl S. (Frontiers in Immunology, 2017)
Peripheral tolerance is an important mechanism by which the immune system can guarantee a second line of defense against autoreactive T and B cells. One autoimmune disease that is related to a break of peripheral tolerance is diabetes mellitus type 1. Using the RIP-GP mouse model, we analyzed the role of the spleen and lymph nodes in priming CD8+ T cells and breaking peripheral tolerance. We found that diabetes developed in splenectomized mice infected with the lymphocytic choriomeningitis virus (LCMV), a finding showing that the spleen was not necessary in generating autoimmunity. In contrast, the absence of lymph nodes prevented the priming of LCMV-specific CD8+ T cells, and diabetes did not develop in these mice. Additionally, we found that dendritic cells are responsible for the distribution of virus in secondary lymphoid organs, when LCMV was administered intravenously. Preventing this distribution with the sphingosine-1-phosphate receptor antagonist FTY720 inhibits the transport of antigen to peripheral lymph nodes and consequently prevented the onset of diabetes. However, in case of subcutaneously infection, administration of FTY720 could not inhibit the onset of diabetes because of the viral antigen is already presented in the peripheral lymph nodes. These findings demonstrate the importance of preventing the presence of antigen in lymph nodes for maintaining tolerance.